The History and Dynamics of Al-Awwabin Islamic Boarding School: From Tradition to a Modern Islamic Educational Institution in Indonesia - Dadang Nur Hidayat; Abdul Rosyid Teguhdin Hamid (Manunggal Halim Jaya, 2026)
Al-Awwabin Islamic Boarding School is an important example of an Indonesian pesantren that developed from a traditional religious study circle into a modern Islamic educational institution. This article examines its establishment, institutional development, leadership dynamics, and educational modernization since Abuya KH. Abdurrahman Nawi initiated the As Shalafiyyah study circle in 1962. The study employs a qualitative historical approach based on a literature review and analysis of online documents. The findings indicate that Al-Awwabin developed gradually through four stages: a traditional study-circle phase, the institutionalization of formal education, branch expansion, and the integration of formal and nonformal education. Its modernization is evident in the establishment of Madrasah Ibtidaiyah (MI), Madrasah Tsanawiyah (MTs), and Madrasah Aliyah (MA); strengthened institutional governance; and the integration of classical Islamic-text studies with general education. The article argues that Al-Awwabin has successfully balanced tradition and modernity, thereby maintaining its relevance as an Islamic educational institution in Indonesia.